Assessment and modification of cardiovascular risk in non-cardiac surgery. Clinical guidelines 2023 - A. N. Sumin; D. V. Duplyakov; F. I. Belyalov; A. E. Bautin; A. V. Bezdenezhnykh; S. V. Garkina; M. L. Gordeev; D. A. Zateishchikov; O. B. Irtyuga; E. V. Korok; T. Yu. Kulagina; E. A. Medvedeva; et al. (Российский кардиологический журнал)
Russian Society of Cardiology (RCS)